Orientation of 2, 6-Dicarbethoxy-3, 5-bis(pyridine-3-yl)tetrahydro-1, 4-thiazine-1, 1-dioxide on Silver Nanoparticles: Surface-Enhanced Raman Spectral Studies. (6th February 2014) - Anuratha, M.; Jawahar, A.; Umadevi, M.; Edayadulla, N.; Sathe, V. G.; Meenakumari, V.; Milton Franklin Benial, A.
Abstract : Silver nanoparticles were synthesized using solution combustion method with citric acid as fuel. The prepared silver nanoparticles exhibit fcc crystalline structure with particle size of ~50 nm. The morphology and purity of the silver nanoparticles were also studied by high-resolution transmission electron microscopy (HRTEM) and energy dispersive X-ray analysis (EDX). Surface-enhanced Raman scattering (SERS) spectra of 2, 6-dicarbethoxy-3, 5-bis(pyridine-3-yl)tetrahydro-1, 4-thiazine-1, 1-dioxide (DBTD) adsorbed on silver nanoparticles were investigated. Orientation of DBTD on silver nanoparticles has been inferred from normal Raman spectrum (nRs) and SERS spectral feature. The observed spectral feature evidenced that DBTD would adsorb on silver surface with tilted orientation through the lone pair electrons of C–N, C=O, S=O, and pyridine ring. The present investigation has been a model system to deduce the interaction of drugs with DNA.